Urbanized and savvy: Which African firms are making the most of mobile money? - Charles Ackah; Aoife Hanley; Lars Hecker; Michael Kodom (Kiel Centre for Globalization (KCG), 2024)
Our analysis of over 500 Ghanaian firms sheds light, for the first time, on how certain firms managed to extract value from mobile money. Our regressions point to the usefulness of this form of cashless payments in stabilizing sales during the COVID pandemic. Perhaps the most important message from our analysis is the recognition that the benefits from mobile money extend beyond its purpose as a tool for transacting cashless payments. We reveal that firms using these additional tools supported by MoMo (e.g. for planning or saving purposes) report higher sales resilience, all things equal. Our findings appear to echo the literature on private householders (e.g. Jack and Suri, 2014). However, while the latter report a positive effect due to remittances, our finding is more likely driven by enhanced ability of businesses to streamline their planning and sales.
Keywords: G23; G21; L25; O14; O18; O33; 330; Mobile Money; Africa; Firm; Urbanization